ON CONTROL EFFECTIVENESS OF ELECTRIC PROCESSES UNDER CUTTING - Anatoly A. Ryzhkin; Victoria E. Burlakova (Advanced Engineering Research)
The effect of thermoelectric heat under cutting is considered. In the narrow feed range under the preselected cu tting speed, no - equalizing current area in the inner electrical circuit is defined